Development of a Multidisciplinary, Multicampus Subspecialty Practice in Endocrine Cancers - Bible, Keith C. (American Society of Clinical Oncology, 2012)
PURPOSE: Relative to more abundant neoplasms, endocrine cancers have been historically neglected, yet their incidence is increasing. We therefore sought to build interest in endocrine cancers, improve physician experience, and develop innovative approaches to treating patients with these neoplasms. METHODS: Between 2005 and 2010, we developed a multidisciplinary Endocrine Malignancies Disease Oriented Group involving all three Mayo Clinic campuses (Rochester, MN; Jacksonville, FL; and Scottsdale, AZ). In response to higher demand at the Rochester campus, we sought to develop a Subspecialty Tumor Group and an Endocrine Malignancies Tumor Clinic within the Division of Medical Oncology. RESULTS: The intended groups were successfully formed. We experienced difficulty in integration of the Mayo Scottsdale campus resulting from local uncertainty as to whether patient volumes would be sufficient to sustain the effort at that campus and difficulty in developing enthusiasm among clinicians otherwise engaged in a busy clinical practice. But these obstacles were ultimately overcome. In addition, with respect to the newly formed medical oncology subspecialty endocrine malignancies group, appointment volumes quadrupled within the first year and increased seven times within two years. The number of active therapeutic endocrine malignancies clinical trials also increased from one in 2005 to five in 2009, with all three Mayo campuses participating. CONCLUSION: The development of subspecialty tumor groups for uncommon malignancies represents an effective approach to building experience, increasing patient volumes and referrals, and fostering development of increased therapeutic options and clinical trials for patients afflicted with otherwise historically neglected cancers.